Ethnography and the Governance of Il/legality: Some Methodological and Analytical Reflections - Werth, Robert (Social justice, 2017)
The article discusses the relationship between governments' criminal justice administration policies, punishment and ethnography, including in regard to ethological methodology. An overview of society's relations with prisons, including ethnological studies on the challenges ex-prisoners face in finding employment, is provided.